Prevalence and correlates of growth failure in young African patients with sickle cell disease. (22nd November 2018) - Alexandre‐Heymann, Laure; Dubert, Marie; Diallo, Dapa A.; Diop, Saliou; Tolo, Aissata; Belinga, Suzanne; Sanogo, Ibrahima; Diagne, Ibrahima; Wamba, Guillaume; Boidy, Kouakou; Ly, Indou Deme; Kamara, Ismaël; et al.
Summary: Growth failure (GF) in children with sickle cell disease (SCD) tends to decline in high‐income countries, but data are lacking in sub‐Saharan Africa. We performed a cross‐sectional study nested in the CADRE (Cœur, Artères et DREpanocytose) cohort in Mali, Senegal, Cameroon, Gabon and the Ivory Coast. SCD patients and healthy controls aged 5–21 years old were recruited ( n  = 2583). Frequency of GF, defined as a height, weight or body mass index below the 5th percentile on World health Organization growth charts, was calculated. We assessed associations between GF and SCD phenotypic group, clinical and biological characteristics and history of SCD‐related complications. GF was diagnosed in 51% of HbSS, 58% of HbSβ 0, 44% of HbSC, 38% of HbSβ + patients and 32% of controls. GF in patients was positively associated with parents' lower education level, male sex, age 12–14 years, lower blood pressure, HbSS or HbSβ 0 phenotypes, icterus, lower haemoglobin level, higher leucocyte count and microalbuminuria. No association was found between GF and clinical SCD‐related complications. In sub‐Saharan Africa, GF is still frequent in children with SCD, especially in males and during adolescence. GF is associated with haemolysis and microalbuminuria, but not with the history of SCD‐related clinical complications.